Treatment Outcomes of Multidrug‑Resistant Tuberculosis Patients in East Java, Indonesia: A Retrospective Cohort Analysis - Indarti, Hardini Tri (Wolters Kluwer, 2022)
Background: The drug regimen for the treatment of multidrug-resistant tuberculosis (MDR-TB) has lower potency, is more costly, and has a greater risk of adverse effects than first‑line anti‑TB drugs. We aimed to compare the treatment outcomes of patients using standard shorter regimen (STR regimen) versus bedaquiline (BDQ)‑containing individual regimen in a high TB‑burden setting. Methods: This was a retrospective cohort study using secondary data from the medical records in the hospital. The study population were patients with MDR-TB who started treatment in 2016–2018. Treatment outcomes were classified as successful (cured/completed treatment) or unsuccessful (failure/death/loss to follow‑up/not evaluated). Categorical data were presented as frequencies and percentage, whereas continuous data were presented as mean ± standard deviations. Risk ratio (RR) was obtained by using the Chi‑square statistical test with 95% confidence interval (CI) and P < 0.05 set as a significant result. Results: We included 99 patients out of 444 registered patients in 2016–2018. The overall success proportion was 41.4%. Success was more likely in patients who received BDQ regimen than those receiving STR regimen (52.9% vs. 35.4%, RR: 1.496, 95% CI: 0.948–2.362). Factors that influenced the treatment outcomes were smear status and sputum culture status. Conclusions: The success rate of the STR regimen and the BDQ regimen in this study is still below the national and global figures due to the high rate of lost to follow‑up. The success was higher in the BDQ regimen, although not statistically significant. Further research is needed on adverse effects, quality of life, and costs during treatment.